2014
DOI: 10.1016/j.neuroimage.2014.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Combat-related blast exposure and traumatic brain injury influence brain glucose metabolism during REM sleep in military veterans

Abstract: Traumatic Brain Injury (TBI), a signature wound of Operations Enduring and Iraqi Freedom, can result from blunt head trauma or exposure to a blast/explosion. While TBI affects sleep, the neurobiological underpinnings between TBI and sleep are largely unknown. To examine the neurobiological underpinnings of this relationship in military veterans, [18F]-fluorodeoxyglucose positron emission tomography (FDG PET) was used to compare mTBI-related changes in relative cerebral metabolic rate of glucose (rCMRglc) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 74 publications
1
34
0
Order By: Relevance
“…Both approaches have further refined our understanding of the localized and neural underpinnings of healthy and disrupted sleep, as well as of circadian variations in brain functions [68][69][70]. The use of neuroimaging methods such as positron emission tomography and structural and functional magnetic resonance imaging during sleep and wakefulness in concussed, recovered, and never concussed individuals remain scarce, but has a high potential to provide unique and novel insights into the underpinnings of sleep and circadian disturbances in mTBI, and therefore may guide the development of innovative and targeted diagnostic and therapeutic strategies [70][71][72][73][74][75].…”
Section: Advanced Sleep Measurement Methodsmentioning
confidence: 99%
“…Both approaches have further refined our understanding of the localized and neural underpinnings of healthy and disrupted sleep, as well as of circadian variations in brain functions [68][69][70]. The use of neuroimaging methods such as positron emission tomography and structural and functional magnetic resonance imaging during sleep and wakefulness in concussed, recovered, and never concussed individuals remain scarce, but has a high potential to provide unique and novel insights into the underpinnings of sleep and circadian disturbances in mTBI, and therefore may guide the development of innovative and targeted diagnostic and therapeutic strategies [70][71][72][73][74][75].…”
Section: Advanced Sleep Measurement Methodsmentioning
confidence: 99%
“…Neuroimaging studies of military service members and veterans have documented chronic abnormalities on 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) imaging, which assesses glucose metabolic activity in the brain (4,22,23). Abnormalities of brain white matter tract structural integrity and myelin density in these veteran populations have also been characterized using magnetic resonance diffusion tensor imaging (DTI) and macromolecular proton fraction mapping (5,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we have found that blast exposure (beyond the effects of PTSD) was associated with reduced cerebral metabolic activity in brainstem, limbic and paralimbic regions, the basal ganglia, and thalamus during REM sleep in veterans with a blast and mTBI exposure compared to those without blast and mTBI exposure. 20 Together, these preliminary observations suggest that attenuation of REM sleep may be an especially sensitive index of central changes resulting from psychological or physical insults. Given the overlap in symptoms of PTSD and TBI, further investigation of REM sleep mechanisms are needed to elucidate the reasons as to why the presence of both blast exposure and PTSD significantly decreased the amount of REM fragmentation when compared to the group in which only blast exposure or PTSD was present.…”
Section: Discussionmentioning
confidence: 80%
“…[55][56][57][58][59][60] Similarly, we have recently reported that blast exposure and/or prior mild TBI was associated with detectable reductions in cerebral glucose metabolism during both wakefulness and REM sleep, despite similar findings on objective measures of sleep continuity and NREM sleep. 20 Probing the functional neuroanatomical correlates of TBI and PTSD separately or when comorbid using sleep neuroimaging methods may reveal group differences during NREM sleep in cerebral perfusion or glucose metabolism relative that are not captured by PSG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation